Synthesis of the Tricyclic Ring Structure of Daphnanes via Intramolecular [4+3] Cycloaddition/SmI2-Pinacol Coupling - Hassan, Ahmed H. E.; Lee, Jae Kyun; Pae, Ae Nim; Min, Sun-Joon; Cho, Yong Seo (AMER CHEMICAL SOC, 2015)
A synthetic approach toward the tricyclic 5,7,6-membered ring structure Of daphnane-family natural products is described. An intramolecular [4 + 3] cycloaddition reaction of furan with an oxypentadienyl cation constructed the oxa-bridged bicyclic structure in a stereoselective fashion. Structural analysis revealed that the desired exo isomer was predominantly acquired through epimerization. Finally, formation of the five-membered ring was achieved through SmI2-mediated pinacol coupling.
Keywords: 1ST SYNTHESIS; TIGLIANE; RESINIFERATOXIN; CYCLOADDITIONS; CONSTRUCTION; PROSTRATIN; DITERPENES; ANALOGS; PHORBOL; POTENT